Perancangan User Experience Prototype Aplikasi untuk Mengatasi Kecemasan Berbicara Didepan Umum - Fasya Yahya; Ratih Kartika Dewi; Lutfi Fanani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
College students in these roles are usually required to be capable of public speaking, such as giving a presentation in front of a class or hosting a big event with a high number of attendees. Many college students are nervous about speaking in public for several reasons, including a fear of being laughed at, a concern about affecting other's perceptions of them, or a poor/bad public speaking experience. As a response, the researchers developed an app to help public speakers reduce anxiety symptoms by providing instructions for breathing and progressive relaxation techniques that can be practiced anywhere. In order to create applications that meet user demands, this design employs the Human-Centered Design methodology. Usability testing was performed on 5 participants during the testing stage. The findings reveal that the efficacy aspect is 88,50%, the efficiency aspect is 0,061 goals/second using the Time-Based Efficiency calculation, and user satisfaction with the SUS questionnaire is 81,80 with an A in the excellent adjective and acceptable. Furthermore, UEQ was used to conduct user experience testing, with the attractiveness aspect scoring 2.16, perspicuity scoring 2.10, efficiency scoring 2.28, dependability scoring 2.15, stimulation scoring 2.39, and novelty scoring 2.10.